(untitled) (Journal of Informatics Education and Research, 2025)
Artificial Intelligence (AI) and chatbot technologies have emerged as transformative tools in the modern financial ecosystem, redefining customer service delivery, operational efficiency, and strategic decision-making in the banking sector. In India, private sector banks have demonstrated rapid adoption of AI-driven digital tools to enhance customer experience, automate routine processes, reduce costs, and strengthen cybersecurity frameworks. The study analysis following specific objectives are: i) to analysed the integration of AI and chatbot technologies in private sector banks in India; ii) to examine growth trends, adoption patterns, and performance outcomes and identifies key determinants influencing implementation success: iii) to suggest suitable policy measures for the strengthening of AI based technologies in banking sector. The study using for the secondary data from academic journals, industry reports, and RBI/SEBI publications, along with qualitative insights from case analyses of major banks, the study highlights how AI innovations—such as Natural Language Processing (NLP), machine learning algorithms, and intelligent conversational bots—are reshaping the banking landscape. The study findings that the AI-enabled chatbots significantly improve service efficiency, customer engagement, operational speed, and risk management. The study concludes that the policy recommendations and future research directions for strengthening AI-enabled digital banking in India.